2004
DOI: 10.1002/eji.200425544
|View full text |Cite
|
Sign up to set email alerts
|

Activation of human neonatal monocyte‐derived dendritic cells by lipopolysaccharide down‐regulates birch allergen‐induced Th2 differentiation

Abstract: Epidemiological studies describe an inverse association between the level of environmental endotoxin exposure during infancy and the prevalence of allergic disease in children. To study the effect of lipopolysaccharide (LPS) and lipopeptide Pam3Cys signaling via Toll-like receptor (TLR)4 and TLR2 on dendritic cells (DC), respectively, on birch allergen-induced T cell differentiation, cord blood monocyte-derived DC were exposed to birch allergen extract alone or in combination with LPS or Pam3Cys and thereafter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 33 publications
3
11
0
Order By: Relevance
“…The production of IL-5 and IFN-␥ was also measured in the cell cultures, but only very low levels of IL-5 and no IFN-␥ were induced, and increased levels were not seen after stimulation (see Fig. S6A and B in the supplemental material), as previously shown with neonatal T cells (4,27).…”
Section: Resultssupporting
confidence: 66%
See 2 more Smart Citations
“…The production of IL-5 and IFN-␥ was also measured in the cell cultures, but only very low levels of IL-5 and no IFN-␥ were induced, and increased levels were not seen after stimulation (see Fig. S6A and B in the supplemental material), as previously shown with neonatal T cells (4,27).…”
Section: Resultssupporting
confidence: 66%
“…To investigate whether sCD14 or sCD83 might modulate neonatal birch allergen-induced T-cell responses, DC were stimulated with birch allergen extract alone or in the presence of sCD14, sCD83, or the control protein HSA and were thereafter cocultured with autologous CD4 ϩ T cells. DC were stimulated in the presence of TNF, IL-1␤, and prostaglandin E 2 , as we have previously shown that DC need to be fully mature to be able to induce birch allergeninduced T-cell expansion and differentiation (4). In order to use physiological doses of sCD14 in our culture systems, the selected concentrations (0.1 or 1 g/ml) were based on the median levels that we have recently found to be present in the circulation during infancy (cord, 0.18 g/ml; 4 months, 0.57 g/ml; 18 months, 0.97 g/ml; 3 years, 0.55 g/ml) (30).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From a practical point of view, the diminished ability of the neonate to produce Th1 responses imparts vulnerability to microbial infections and the bias towards Th2 cells confers susceptibility to allergic reactions. Thus, understanding the mechanisms underlying the simultaneous Th1 unresponsiveness and robust Th2 function of the neonate represents a prerequisite for the development of pediatric vaccines and strategies against allergies [32, 33]. As there is no specific surface marker which can unambiguously distinguish Th1 from Th2 cells, we used the neonate-to-neonate T cell transfer model described above to trace primary Th1 and Th2 cells and analyzed their phenotypes upon initial contact with Ag as well as their fate upon re-exposure to Ag (Figure 2) [23].…”
Section: Neonatal Th1 Immunity: Imprinted Attributes and The Inabilitmentioning
confidence: 99%
“…This type of early-life-stage–restricted immunotoxicity appears to contribute to an increased risk of atopy and asthma. Andersson et al (2004) showed that maturation of newborn immature dendritic cells with LPS reduced the development of a T H 2-associated birch allergen response. In contrast, the lack of dendritic cell maturation from the fetal immature stage was associated with children at risk for type 1 diabetes (Skarsvik et al 2004).…”
Section: Thymic Generation Of Regulatory T-cells (Cd4+cd25+ High Exprmentioning
confidence: 99%